Formulation and characterization of α-mangostin in chitosan nanoparticles coated by sodium alginate, sodium silicate, and polyethylene glycol - Nasrul Wathoni; Agus Rusdin; Erma Febriani; Destiana Purnama; Wahnidar Daulay; Sundoro Y Azhary; Camellia Panatarani; I Made Joni; Ronny Lesmana; Keiichi Motoyama; Muchtaridi Muchtaridi (Wolters Kluwer Medknow Publications, 2019)
Context: α-mangostin, one of the xanthone derivative compounds isolated from Garcinia mangostana L. peel extract, has an excellent anticancer efficacy. However, α-mangostin has a lack of site specificity, poor cells selectivity, and low aqueous solubility. Polymeric nanoparticles formulation can be used to solve these problems. Aim: Therefore, the main aim of this study was to develop polymeric nanoparticles of α-mangostin-based chitosan (αM-Ch) coated by sodium alginate (αM-Ch/Al), sodium silicate (αM-Ch/Si), and polyethylene glycol 6000 (αM-Ch/PEG). Materials and Methods: Polymeric nanoparticles were prepared by ionic gelation method with the spray pyrolysis technique. Optimized formula was characterized by scanning electron microscopy, particle size, entrapment efficiency, drug loading, Fourier transform infrared, X-ray diffraction (XRD), and differential scanning calorimetry (DSC). Results: αM-Ch/Al, αM-Ch/Si, and αM-Ch/PEG Nanoparticles were successfully prepared with the range of particle size approximately 200-400nm. The XRD patterns and DSC thermograms of αM-Ch/Al showed an amorphous state, whereas αM-Ch/Si and αM-Ch/PEG indicated low crystalline forms. In addition, αM-Ch/Al had the highest entrapment efficiency (98.33% ± 0.06%) compared to αM-Ch/Si (70.46% ± 8.93%), and αM-Ch/PEG (92.24% ± 10.98%). Conclusion: These results suggest that αM-Ch/Al has the potential to enhance the physicochemical properties of α-mangostin for further formulation as an anticancer agent.